Twisted intramolecular charge transfer of nitroaromatic push–pull chromophores - Lee, Sebok; Jen, Myungsam; Jang, Taehyung; Lee, Gisang; Pang, Yoonsoo (Scientific reports, 2022)
The structural changes during the intramolecular charge transfer (ICT) of nitroaromatic chromophores, 4-dimethylamino-4′-nitrobiphenyl (DNBP) and 4-dimethylamino-4′-nitrostilbene (DNS) were investigated by femtosecond stimulated Raman spectroscopy (FSRS) with both high spectral and temporal resolutions. The kinetically resolved Raman spectra of DNBP and DNS in the locally-excited and charge-transferred states of the S 1 state appear distinct, especially in the skeletal vibrational modes of biphenyl and stilbene including ν 8a and ν C=C . The ν 8a of two phenyls and the ν C=C of the central ethylene group (only for stilbene), which are strongly coupled in the planar geometries, are broken with the twist of nitrophenyl group with the ICT. Time-resolved vibrational spectroscopy measurements and the time-dependent density functional theory simulations support the ultrafast ICT dynamics of 220–480 fs with the twist of nitrophenyl group occurring in the S 1 state of the nitroaromatic chromophores. While the ICT of DNBP occurs via a barrier-less pathway, the ICT coordinates of DNS are strongly coupled to several low-frequency out-of-phase deformation modes relevant to the twist of the nitrophenyl group.